Strategy and Multinational Organization Structure: An Interorganizational Relationships Perspective - Herbert, Theodore T. (Academy of Management Review, 1984)
Traditional rationales for multinational organizational structures have emphasized top-down design parameters rather than linkages between geographically dispersed units and basic internationalization objectives. A basis for structural variation by resource flow considerations (Pfeffer & Salancik, 1978) is derived and is used to develop a tentative model of strategy-and-structure configurations. Under defined conditions, the several multinational structures are hypothesized to be related to identified strategies.